Cloud and Fog Computing: A Survey to the Concept and Challenges - Raza, Muhammad Raheel; Varol, Asaf; Varol, Nurhayat (Institute of Electrical and Electronics Engineers Inc., 2020)
Cloud Computing is one of the most emerging technologies that has transformed the macro world. The advent of cloud computing is not less than an evolution and miracle to the technology. It has made the on-demand availability of various scalable software resources possible over the internet. Although its extraordinary services and advantages like reduction of computing and storage resources as well as reducing cost, there are some barriers that limits and challenges the usability of cloud computing. On the other hand, Fog Computing, another computing paradigm, is an extended and advanced version of cloud computing. Having distributed nature, Fog Computing tries to address the limitations faced by cloud computing. The paper provides a general study of the challenges faced by cloud computing and how fog computing infrastructure serves to be an emerging technology to those limitations. © 2020 IEEE.
8th International Symposium on Digital Forensics and Security, ISDFS 2020 -- 1 June 2020 through 2 June 2020 -- Beirut -- 161222
Keywords: cloud; cloud computing; computing paradigms; fog; fog computing; IOT